PEMBUATAN WEB MENCARI RESTORAN DI LAMPUNG DENGAN WEIGHTED PRODUCT - Billy Alexander Suherli; Desi Arisandi; Manatap Dolok Lauro (Jurnal Ilmu Komputer dan Sistem Informasi, 2019)
Website has been made to help toursists to find restaurant in Lampung. Futhermore, tourist can also filtering the restaurant by inputing some categories that has been placed by Writer. For the Compare feature, system is using Weighted Product as a support system to decide which restaurant is better. Tourists can choose restaurants from 2 up to 5, after that Weighted Product will Calculate and put rank in each restaurants that has been chosen to be compared.